Analysis of EPCAM protein expression in diagnostics of Lynch syndrome - Kloor, Matthias; Voigt, Anita Yvonne; Schackert, Hans K.; Schirmacher, Peter; Knebel Doeberitz, Magnus von; Bläker, Hendrik (Journal of clinical oncology, 2011)
Purpose: Lynch syndrome is an inherited tumor predisposition syndrome caused by germline mutations of DNA mismatch repair (MMR) genes, mainly MLH1 and MSH2. Recently, germline deletions affecting the epithelial cell adhesion molecule (EPCAM) gene located upstream of MSH2 were identified as a novel mutational mechanism causing Lynch syndrome by epigenetic inactivation of the respective MSH2 allele. Immunohistochemical analysis of MMR protein expression is a hallmark of Lynch syndrome diagnostics, but it cannot distinguish between EPCAM deletion carriers and MSH2 mutation carriers. We hypothesized that EPCAM protein expression might be altered in tumors from patients with a germline EPCAM deletion. - Patients and Methods: Immunohistochemistry was used to assess EPCAM expression in Lynch syndrome-associated MSH2-negative tumors (n = 26). Multiplex ligation-dependent probe amplification (MLPA) analysis was performed to detect germline deletions of the EPCAM and MSH2 gene loci. - Results: In four MSH2-negative tumors, a concomitant lack of EPCAM expression was detected. MLPA analysis revealed heterozygous EPCAM deletions in all patients with EPCAM-negative tumors. In contrast, EPCAM expression was positive in all cancers from patients with germline alterations affecting MSH2 but not EPCAM. Two EPCAM deletions were detected in patients with an EPCAM-positive tumor. - Conclusion: These results indicate that loss of EPCAM protein expression is frequent in tumors from patients with EPCAM germline deletions. EPCAM immunohistochemistry therefore represents a promising novel tool for the identification of Lynch syndrome patients with EPCAM germline deletions.